Product Checker Mobile Application Using Augmented Reality (SNEAKICKS) - Mohamad Fauzi, Danial Zaki; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2021)
SNEAKICKS application is a platform to help users find out accurate information about sneakers using augmented reality technology. Today there are some applications that do not provide information about sneakers as well as the tendency of employees in the store that provide less accurate information to customers about sneakers. The objective of this project is to design and develop applications using 3D methods based on mobile application platform to assist users in knowing information about sneakers and subsequently test SNEAKICKS application on target users who want to own and learn about sneakers. In developing this application, the methodology used is Multimedia Mobile Content Development (MMCD) which has five phases which are application idea creation, analyse the structure, design the process, develop main function and testing because it is easy to understand and simple. especially when each process is completed without any overlap. The application was developed using Marker-Based augmented reality (Vuforia) to display 3D models based on detected images. The application was tested and shows that it can give the user the freedom to control the 3D model such as changing the position as well as can provide information about the interior design of the sneakers which in turn helps users in knowing information about sneakers as expected. Beta test analysis showed the SNEAKICKS app was fully functional as expected. In addition, user acceptance of this application is very good and satisfactory.